Free Learning To End Educational Feudalism - Regina Mamuko; Sugijanti Supit; Yefta Emor (Didaskalia: Jurnal Pendidikan Agama Kristen, 2023)
The dominance of culture of feudalism is still inherent inlearning practices in Indonesia. In the context of education, feudalismreflects authoritarian, hierarchical, and centralistic practices in whichteachers or educators are considered a single authority that must berespected without much space for active participation and studentindependence. To respond to this problem, the Indonesian governmenthas launched an initiative known as "Independent Learning". This studyaims to show that the independent learning curriculum can be the answerto the problem of feudalism in learning. This research was conductedusing the literature study method. Literature study was conducted byreviewing books and articles related to the title. The results of this studyindicate that the independent learning curriculum can be an effective toolto promote critical thinking, independence, and equality in education.Thus, the independent learning curriculum can be a strong tool to breakthrough feudalism in learning. By giving freedom to students to regulatetheir own learning, promote critical thinking, independence, andequality, a learning environment can be created more inclusive, dynamic,and responsive to student needs.